2014
DOI: 10.11604/pamj.2014.17.186.2363
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multiple drug resistance and biofilm formation in Staphylococcus aureus isolated from medical and non-medical personnel in Yaounde, Cameroon

Abstract: IntroductionMonitoring the prevalence of nasal carriage of multiple drug resistance (MDR) Staphylococcus aureus (SA) strains in hospital personnel is essential. These strains when transmitted from hospital personnel to patients with already weakened immune states or in-built medical devices, may limit the latter's treatment options. This study aimed at assessing the potential exposure of patients to these MDR SA in a resource-limited hospital setting by assessing the prevalence and relationship between antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
3
23
1
1
Order By: Relevance
“…This may be a sign that their biofilm forming ability is simultaneously influencing the resistance pattern of the isolates or have been masked, since most of the isolates already harbour resistant genes to the antibiotics tested. This result is in line with the study of Eyoh [24] where they recorded highest prevalence of 35.6% from weak biofilm-formers in isolates of both medical and non-medical personnel.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be a sign that their biofilm forming ability is simultaneously influencing the resistance pattern of the isolates or have been masked, since most of the isolates already harbour resistant genes to the antibiotics tested. This result is in line with the study of Eyoh [24] where they recorded highest prevalence of 35.6% from weak biofilm-formers in isolates of both medical and non-medical personnel.…”
Section: Discussionsupporting
confidence: 91%
“…Cameroun also stated that there was no significant difference in the percentage of MDR among biofilm producers and non-biofilm producers for both medical and non-medical personnel [24]. Although, Fitzpatrick [25] has found more MDR strains among biofilm producers than non-biofilm producers.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, multiple studies have yielded conflicting results. For example, while Abidi et al studied 22 Pseudomonas aeruginosa isolates and concluded that biofilm production was significantly higher in MDR isolates (Abidi et al, 2013 ), Atashili et al failed to find a significant difference in biofilm formation among MDR and non-MDR Staphylococcus aureus (Atashili et al, 2014 ). For A. baumannii , while Gurung et al studied 60 isolates and found a positive relationship between biofilm formation and antibiotic resistance (Gurung et al, 2013 ), Perez studied 116 isolates and detected an inverse one between meropenem resistance and biofilm production (Perez, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are associated with recurrent infections that are difficult to treat because of their recalcitrance to antibiotics. In vitro studies assessing growth dynamics and antibiotic tolerance of biofilms have typically been performed with single species (Sena et al 2006;Ito et al 2009;Abidi et al 2013;Duus et al 2013;Eyoh et al 2014;Vuotto et al 2014;Moghadam et al 2014;Qi et al 2016). However, bacteria coexist in nature, and under pathological conditions, to form communities that feature advanced synergistic and antagonistic interactions, influencing growth and metabolism of other species (Haruta et al 2009).…”
Section: Introductionmentioning
confidence: 99%